OCCUPATIONAL STRESS AS A MEDIATOR IN THE RELATIONSHIP BETWEEN JOB SATISFACTION AND MOTIVATION AMONG SCHOOL TEACHERS IN THE SULTANATE OF OMAN - Ali Sulaiman Talib Al Shuaili, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study investigates the relationship between occupational stress, job satisfaction, and motivation among schoolteachers in the Sultanate of Oman, focusing on the mediating role of occupational stress. Conducted during the 2023–2024 academic year, the research involved 725 teachers from public schools across various governorates. The study adopted a descriptive correlational design and utilized a validated survey questionnaire comprising three standardized scales: the Occupational Stress Scale (Kanwal, Rafiq, & Afzal, 2023), the Job Satisfaction Scale (Skaalvik & Skaalvik, 2015), and the Motivation Scale (Abós, Sevil, Martín-Albo, Aibar, & García-González, 2018). The results indicate that workload and administrative tasks are the primary contributors to occupational stress, which negatively impacts job satisfaction and motivation. Mediation analysis revealed that occupational stress significantly reduces the positive influence of job satisfaction on motivation, highlighting its critical role in the teacher experience. The study's findings underscore the need for targeted interventions to reduce stressors, such as workload management, enhanced administrative support, and improved resource availability. Recommendations include the introduction of stress management programs, policy reforms to address teacher workload, and recognition initiatives to boost morale. These measures aim to create a supportive work environment, enhancing teacher satisfaction and motivation while contributing to the improvement of Oman’s education system. This study emphasizes the importance of prioritizing teacher well-being to achieve educational excellence and national development goals.